Mitigation Sexual Violence Against Children in Aceh - Roslaili, Yuni; Ulfah, Marina; Suparwany; Muzaky, Muhammad; Aisyah, Siti (Hikmatuna : Journal for Integrative Islamic Studies, 2024)
Although Aceh had issued a number of regulations concerning sexual violence against children, the trend of sexual abuse in Aceh has tended to increase annually. This article investigated the Aceh government's response to child sexual abuse cases through the Banda Aceh Municipal UPTD PPA as instructed by Qanun No. 9/2019. This article relied on qualitative research, using case studies and in-depth interviews about the Aceh sexual violence victims' treatment from their advocates at the UPTD PPA office in Banda Aceh. The interviews were intended to analyse the implementation of Qanun No. 9/2019 on the Implementation of Response to Violence against Women and Children in Aceh.  This study concluded that the implementation of Aceh Qanun number 9 of 2019 concerning the organizing and addressing violence against children had not been well carried out and had not yet been efficient. It was evidence that although Aceh had passed a number of regulations on the prevention of sexual violence against children, including Qanun Aceh number 9 of 2019, the local government had not yet issued technical guidelines for implementation; therefore, relevant agencies currently not working collaboratively in dealing with children's sexual abuse cases in Aceh and remained working in a sectoral manner. In addition, the community and parents were less motivated to report cases of sexual abuse that occurred in their environment because it was seen as a disgrace. In addition, child victims often experience mental decline, thereby making it difficult to obtain information about what had happened to them.